A Delphi Study to Detect Deficiencies and Propose Actions in Real Life Treatment of Neovascular Age-Related Macular Degeneration - Alfredo García-Layana; Luis Arias; Marta S. Figueroa; Javier Araiz; José María Ruiz-Moreno; José García-Arumí; Francisco Gómez-Ulla; María Isabel López-Gálvez; Francisco Cabrera-López; José Manuel García-Campos; Jordi Monés; Enrique Cervera; et al. (Journal of Ophthalmology)
Purpose. Spanish retina specialists were surveyed in order to propose actions to decrease deficiencies in real-life neovascular age macular degeneration treatment (nv-AMD). Methods. One hundred experts, members of the Spanish Vitreoretinal Society (SERV), were invited to complete an online survey of 52 statements about nv-AMD management with a modified Delphi methodology. Four rounds were performed using a 5-point Linkert scale. Recommendations were developed after analyzing the differences between the results and the SERV guidelines recommendations. Results. Eighty-seven specialists completed all the Delphi rounds. Once major potential deficiencies in real-life nv-AMD treatment were identified, 15 recommendations were developed with a high level of agreement. Consensus statements to reduce the burden of the disease included the use of treat and extend regimen and to reduce the amount of diagnostic tests during the loading phase and training technical staff to perform these tests and reduce the time between relapse detection and reinjection, as well as establishing patient referral protocols to outside general ophthalmology clinics. Conclusion. The level of agreement with the final recommendations for nv-AMD treatment among Spanish retinal specialist was high indicating that some actions could be applied in order to reduce the deficiencies in real-life nv-AMD treatment.